Involvement of sympathetic reflex activity in patients with acute and chronic stroke: A comparison with functional motor capacity - TÜRKDOĞAN, DİLŞAD; AKYÜZ, GÜLSEREN DERYA (W B SAUNDERS CO-ELSEVIER INC, 2004)
Objective: To investigate sympathetic nervous system functions in patients with acute and chronic phase of stroke by measuring sympathetic skin reflex (SSR) and the relationship between sympathetic dysfunction and motor function capacity. Design: Cross-sectional, case-control study. Setting: A physical medicine and rehabilitation department in a research hospital of a university referral center in Turkey. Participants: Fifty-six patients with stroke-13 in the acute phase and 43 in the chronic phase-and 42 age- and sex-matched healthy volunteers were included. Intervention: SSR was recorded with electric stimulation of the bilateral median nerves. Main Outcome Measures: SSR was recorded to assess sympathetic reflex activity in patients in the acute and chronic phase of stroke and in controls. Motor functions was classified using the Brunnstrom stages. Results: The mean SSR latency in the acute phase was significantly prolonged and the amplitudes were decreased compared with controls. In the chronic phase, the mean amplitudes were significantly attenuated compared with controls, whereas the mean latency did not change. The mean latency of SSR in patients in Brunnstrom groups 1 and 2 was longer, and the mean amplitude was smaller than in controls (P<.05). The mean amplitude was significantly reduced in patients classified as Brunnstrom groups 3 and 4 compared with controls (P<.05), but the mean latency was not affected. Conclusions: Depression of sympathetic reflex activity was more prominent in the acute phase of stroke and was associated with moderate or highly limited motor function capacity. Improvement of motor dysfunction may parallel recovery of sympathetic reflex activity.
Keywords: autonomic nervous system; galvanic skin response; rehabilitation; stroke; RR INTERVAL VARIATION; SKIN-RESPONSE; BRAIN INFARCTION; NERVOUS-SYSTEM; REPRODUCIBILITY; LESIONS